KEKOSONGAN NORMA DALAM PENGENAAN SERVICE CHARGE DI INDUSTRI RESTORAN : ANALISIS YURIDIS TERHADAP PERLINDUNGAN KONSUMEN” - Syarifudin Hamzah (Jurnal Perspektif Hukum, 2026)
The practice of imposing a service charge in the restaurant industry in Indonesia has become increasingly common; however, it lacks explicit legal regulation within the existing statutory framework. This study aims to analyze the legal framework governing service charges and examine the implications of normative gaps on consumer protection under Law Number 8 of 1999 on Consumer Protection. This research employs a normative juridical method using statutory, conceptual, and case approaches, supported by primary, secondary, and tertiary legal materials analyzed qualitatively. The findings indicate that a service charge does not constitute a legally binding levy such as tax, and its application should be based on consumer consent and the principles of transparency and good faith. In practice, however, service charges are often imposed unilaterally through standard clauses without explicit consumer agreement, potentially violating Articles 4, 7, 10, and 18 of the Consumer Protection Law. This normative gap weakens consumer protection, particularly regarding the right to information, fairness, and legal certainty, and creates opportunities for misleading and non-transparent business practices. Therefore, more comprehensive legal regulation is required to govern service charges in order to ensure a balance between business interests and consumer rights.